Disability and Its Correlates in a Developing Country Context: Evidence from Multiple Datasets and Measures. Issue 4 (3rd April 2018) - Priebe, Jan
Abstract : Disability profiles showing how the magnitude of disability differs across subgroups of a population are important tools in designing effective policies. Yet little is known about the sensitivity of the correlates of disability to the way disability is measured. This study uses an unprecedentedly large amount of nationally representative survey data from Indonesia. Based on 13 different datasets that were collected between 2000 and 2014, and which together contain disability information on more than 1 billion individuals, we assess how robust disability profiles are to measurement issues. Our findings suggest that irrespective of the dataset and measure used, disability is disproportionally more common among the poor, the elderly and rural areas in the country. Hence, Indonesian policies on poverty reduction, population ageing, and rural development should pay particular attention to how they reach and affect persons with disabilities. Our research further reveals that the gender gap in disability is highly sensitive to measurement issues with different datasets and measures reaching different conclusions about the size and direction of the gap.